International financial management (London : International Thomson Business Press, 1993)
This book is divided into four parts: Foreign exchange management; Cost of capital; Financial structure; and Capital busgeting.
Keywords: Finance; Business enterprises; International business enterprises -- Finance; International finance; Foreign exchange